Ecological considerations on the lake Bolonha zooplankton, Belém, Pará, Brazil - de Melo, Nuno Filipe Alves Correia; Paiva, Rosildo Santos; da Silva, Mauro Márcio Tavares (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2006)
Zooplankton population of the lake Bolonha were sampled in three stations in September of 1993. The objective was to determine the basic characteristics of the populations, as the composition and density of species, besides some environmental parameters. Fifty six species were determined, thirty of them were of Rotifera, nineteen Cladocera and seven Copepoda. Among Rotifera, the most frequent organisms were Brachionus zahniseri gessneri, Polyarthra vulgaris and Tricocerca similis, while enter Cladocera, Bosminopsis deitersi and Bosmina hagmanni were the most important in density terms. For Copepoda, the nauplii and copepodits they were the ones that presented the largerst densities, but Oithona amazonica and Notodiaptomus amazonicus deserve to be registered for they have also presented a great density. The lake Bolonha came with a great diversity of zooplanktonic organisms, needing, meantime of more intensive studies, because that number in biodiversity terms should increase considerable.
Keywords: Zooplankton; Amazon; Bolonha lake; Utinga; Limnology